Konsep Tujuan Pendidikan Islam Perspektif Nilai-nilai Sosial-kultural - Miftahur Rohman; Hairudin Hairudin (Universitas Islam Negeri Raden Intan Lampung, 2018)
Islamic education as part of the national education system has a goal to be achieved. In the process, Islamic education can not be separated from the problems faced. In today's postmodern era, Islamic education should be used as a container for the seeds of tolerance to maintain harmony and peace. AlQuran and Hadith as the main source of Islamic education should be reinterpreted and integrated with other approaches. One approach that can be integrated is to internalize the socio-cultural values in learning. This approach offers a synthesis in order to face the seeds of intolerance that have begun to grow in this nation's young generation. With the internalization of these values are expected to create a social harmony that can be made provision by the young generation of Muslims in public life.